PENGEMBANGAN INSTRUMEN DAN PENGUJIAN PROPERTI PSIKOMETRI SKALA MODERASI BERAGAMA DI PERGURUAN TINGGI - Yonathan Natanael; Zulmi Ramdani (Balai Diklat Keagamaan Bandung, 2021)
This study aims to formulate and test the scale of religious moderation which is created to measure condition of students’ religious moderation at the higher-education level. Quantitative research method of measuring construction model is used to create a psychological scale that measures students’ religion moderation. Purposive sampling techniques were conducted in this study and compiled 470 as active respondents. The results show that the scale of religious moderation made meets the experts validation and have discrimination power that meets the prerequisites of psychometric properties. The reliability coefficient of religious moderation scale is 0.804 (highly reliable) and confirmatory factor analysis shows that the scale meets the fit model as a good measuring instrument. This study provides religious moderation scale that can be used to identify religious moderation condition especially for students.Keywords: religious moderation; religious measurement; psychometric properties; religious moderation scale; religious tolerance.